2013
DOI: 10.1016/j.stemcr.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Human Developmental Chondrogenesis as a Basis for Engineering Chondrocytes from Pluripotent Stem Cells

Abstract: SummaryJoint injury and osteoarthritis affect millions of people worldwide, but attempts to generate articular cartilage using adult stem/progenitor cells have been unsuccessful. We hypothesized that recapitulation of the human developmental chondrogenic program using pluripotent stem cells (PSCs) may represent a superior approach for cartilage restoration. Using laser-capture microdissection followed by microarray analysis, we first defined a surface phenotype (CD166low/negCD146low/negCD73+CD44lowBMPR1B+) dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(133 citation statements)
references
References 31 publications
(22 reference statements)
9
122
0
1
Order By: Relevance
“…In our previous study, high expression of the Oprk1 gene encoding KOR was shown in developing human limbs (17). However, no skeletal phenotype was found in Oprk1 -/-mice (19).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In our previous study, high expression of the Oprk1 gene encoding KOR was shown in developing human limbs (17). However, no skeletal phenotype was found in Oprk1 -/-mice (19).…”
Section: Discussionmentioning
confidence: 90%
“…We have previously reported a number of genes that are enriched in human cartilage-committed mesenchymal cells (prechondrocytes) by microarray analysis when comparing prechondrocytes with total limb cells (17). The gene encoding KOR, Oprk1, showed the highest enrichment relative to other genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify compounds that could inhibit hypertrophy, we isolated total limb cells from Col10a1 -mCherry mice27 and cultured them in the presence of bone morphogenetic protein (BMP)-4, a driver of developmental chondrocyte hypertrophy;28 170 000 compounds were assayed for their ability to decrease the mCherry signal (figure 1A). Seventy-five were chosen for follow-up (figure 1B), and additional vetting based on reproducibility and magnitude of Col10a1 inhibition led to the selection of regulator of cartilage growth and differentiation (RCGD) 423 for continued characterisation (figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…La organización microestructural de estos componentes confiere al cartílago sus propiedades anatómicas y funcionales, siendo el colágeno tipo II y el agrecano las moléculas más abundantes e importantes del cartílago hialino articular (Maroudas et al, 1998). Cuando el cartí-lago hialino se daña es reemplazado por fibrocartílago, el cual contiene colágeno tipos I y II y posee características morfológicas y funcionales diferentes (Wu et al, 2013).…”
Section: Características Del Cartílago Articularunclassified